POTENSI EFEK HIPOGLIKEMIK KOMBINASI EKSTRAK ETANOL UMBI BAWANG HUTAN (Eleutherine bulbosa) DAN KULIT BATANG KAYU MANIS (Cinnamomum burmanii) PADA TIKUS (Rattus norvegicus) DIABETES YANG DIINDUKSI STREPTOZOTOSIN DAN TOLERANSI GLUKOSA - Devyayu Prabaningsih; Yuliet Yuliet; Ririen Hardani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
Research on potential hypoglycemic effects of ethanol extract combination of onion forest bulbs (Eleutherine bulbosa) and burmani cortex (Cinnamomum burmanii) in streptozotocin (STZ)-induced diabetic and glucose tolerant rats (Rattus norvegicus) has been conducted. This study aimed to determine the hypoglycemic effect and the effective dose of ethanol extract combination of forest onion bulbs and cinnamon cortex. Extract was obtained by maceration using 96% ethanol. A number of 30 male rats were divided into 6 groups and each group consisted of 5 rats. The first group (negative control) was given Na.CMC; the second group (positive control 1) glibenclamide 0.45 mg/kgBW; the third group (positive control 2) acarbose 9 mg/kgBW; while the 4th, 5th, and 6th were successively given combination of ethanol extract of forest onion bulbs and cinnamon cortex at doses of 100+100, 50+50, and 25+25 mg/kgBW. Each rat group was intraperitoneally (ip) induced with STZ 40 mg/kgBW and then treated for 14 days, after the rats developed diabetic condition, glucose tolerance test was performed with the induction of sucrose 150mg/kgBW which was continued with observation in minute 60, 90, 120, 150, and 180. Treatment data were analyzed using ANOVA (analysis of variance) with 95% confidence interval. The results showed that ethanol extract combination of forest onion bulbs and cinnamon cortex had potential hypoglycemic effects in male rats of which the most effective combination dose was at a dose of 50 + 50 mg/kgBW